1999
DOI: 10.1016/s0147-1767(99)00003-6
|View full text |Cite
|
Sign up to set email alerts
|

Communicating information in conversations: a cross-cultural comparison

Abstract: ABSTRACT. The purpose of this study was to compare the amount of information sent by the speaker, received and retrieved by the listener in inter-and intra-cultural conversations. Three hypotheses were tested: (1) in their conversations, inter-cultural interactants would communicate signi®cantly less information than intra-cultural interactants with other variables held constant, (2) the two inter-cultural conditions would not be dierent from each other in terms of the amount of information communicated, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 36 publications
0
44
0
1
Order By: Relevance
“…Univariate F-test showed that no two groups were significantly different from each other, Table 1, the four groups had similar speaker presentation scores but very different listener recall scores. Detailed analyses of speaker presentation and listener recall scores are presented elsewhere (Li, 1999a). All dyads were same-gender; males and female were evenly distributed in all conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Univariate F-test showed that no two groups were significantly different from each other, Table 1, the four groups had similar speaker presentation scores but very different listener recall scores. Detailed analyses of speaker presentation and listener recall scores are presented elsewhere (Li, 1999a). All dyads were same-gender; males and female were evenly distributed in all conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The smallest string of words with meaning was the unit of analysis (Bales, 1950;Li, 1999a;Roter & Hall, 1992). Each unit of information was worth 4 points.…”
Section: Scoring Of Listener Recall and Speaker Presentationmentioning
confidence: 99%
“…El tipo de conocimiento que predomina en las comunidades epistémicas es relativamente esotérico y formalizado (codificado), por lo que para pertenecer a dicha comunidad es preciso compartir las bases nucleares del conocimiento que se produce en su interior. Nuevamente, sin un sistema común de comunicación, la transferencia de conocimiento (y con ello la futura creación de ideas) es un proceso limitado o inexistente ya que los miembros recibirán mensajes sin entenderlos (Li, 1999). En la medida en que el conocimiento que predomina en las comunidades epistémicas es explicito (codificado) la cercanía física de sus miembros es menos relevante y es más frecuente encontrar que las comunidades epistémicas tiene un carácter global (Coe y Bunnell, 2003;Ponds et al, 2007;Hussler y Rondé, 2007).…”
Section: Conclusionesunclassified
“…Clarity and precision in the information delivered provide the basis for accurate and accessible information retrieval. Studies on information transmission and recollection have shown that in intercultural exchanges listeners can typically retrieve only 50% of the information delivered by the speaker or 25% less than the information retrieved in intracultural exchanges (Li, 1999a).…”
Section: A Ck N O W Led G Em En Tsmentioning
confidence: 99%
“…Nevertheless, to initiate the repairing sequences in intercultural encounters, the nonnative listener requires being quite aware of the possibilities of miscommunication in intercultural communication (Erickson, 1975;Gass & Varonis, 1991;Gumperz, 1978;Li, 1999a;Tannen, 1981). Studies of repairing conversational errors have found that native speakers usually take the role of repairing or correcting inaccuracies in the information.…”
Section: Reducing Misunderstandings In the Communicationmentioning
confidence: 99%